Kinetic and physicochemical modeling of β-galactosidase from Rhynchophorus palmarum larvae - Sobamfou Marius Kambiré; Mankambou Jacques Gnanwa; David Boa; N’guessan Eugène Jean Parfait Kouadio; Bonito Aristide Karamoko (PLoS ONE, 2026)
Palm weevil ( Rhynchophorus palmarum L.) is a significant pest that has been identified as a threat to palm trees in tropical regions. Beyond its agricultural impact, its digestive system represents a promising source of biocatalysts. The present study investigates the catalytic activity of β -galactosidase extracted from the digestive juice of R. palmarum larvae. o -nitrophenyl- β -D-galactopyranoside ( o NPG) was utilized as the substrate in this investigation. The purified enzyme exhibited optimal activity at 330.0 ± 1.2 K and pH = 5.0 ± 0.1, as determined by empirical and mechanistic models. The activation energy (E a ) was estimated at 56.3 ± 9 kJ mol -1 using mechanistic models. Furthermore, the pK values for the enzyme-substrate complex were determined to be 4.0 ± 0.1 for the nucleophile and 6.2 ± 0.2 for the proton donor, which provides insight into the catalytic residues. Kinetic analysis through nonlinear regression yielded a catalytic constant (k cat ) of 4.9 × 10 3 s -1 with V max and K m values of 49 ± 2 U mg -1 and 0.77 ± 0.08 mM, respectively. The results obtained provide novel insights into the physicochemical properties of this enzyme. The findings of this study demonstrated that the insect digestive system is a promising and largely untapped source of robust β -galactosidases with considerable potential for industrial biocatalytic applications.